How Schools Can Impact Student Retention Among First Nations Students Leading to Higher Graduation Rates? - Beebe, Clarice (Graduate Studies, 2013)
This study examines how schools can impact student retention among First Nations students and bring about higher graduation rates. The perceptions and perspectives of eight high school students were examined to discover how effective schools were in helping them succeed academically. First Nations student graduation rates are statistically low across Canada. In 1996, Statistics Canada revealed that 60 percent of First Nations on-reserve residents aged 20-24 had not completed high school or obtained an alternative diploma or certificate (Mendelson, 2008). The 2006 Census results that were released 10 years later reported no change in the data on high school completion among First Nations youth. The researcher conducted a qualitative study in 2011 in order to acquire the perspectives and perceptions of the participants regarding their high school experiences. The study sought to identify what factors in the school positively influenced them and at the same time what barriers they encountered and how the school addressed these. Internal structures such as school leadership, teachers, support staff, and school programming were important factors in the academic success of these students. Significantly, this study found that educational attainment among students is dependent upon effective school structures such as school leadership, teachers, and school programs that make quality schools. School structures must be responsive to the diversity of the student population. In the case of First Nations or Aboriginal students, most schools clearly made a concerted effort to recognize student diversity. Also important is that schools must be prepared to meet this challenge by planning for and implementing appropriate structures that support Aboriginal students as they work towards completing high school. Important issues such as racism and discrimination were evident in several of the schools. The outcome of this research provides recommendations and conclusions to further student retention for the Aboriginal or First ...